2019
DOI: 10.1002/aps3.1227
|View full text |Cite
|
Sign up to set email alerts
|

Open‐source data reveal how collections‐based fungal diversity is sensitive to global change

Abstract: Premise of the Study Fungal diversity (richness) trends at large scales are in urgent need of investigation, especially through novel situations that combine long‐term observational with environmental and remotely sensed open‐source data. Methods We modeled fungal richness, with collections‐based records of saprotrophic (decaying) and ectomycorrhizal (plant mutualistic) fungi, using an array of environmental variables across geographical gradients from northern to centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 55 publications
4
32
1
Order By: Relevance
“…However, our models suggest that the very strong temperature increase under the high-emission scenario (RCP8.5), together with the cumulative likelihood of summer droughts 27 , will suppress fruit body formation (and thus total production) 20 , regardless of the sporocarp's ability to survive under extreme aridity. Hence, we expect that the most favourable climate conditions will move northward, which coincides with the predicted latitudinal shift reported in Büntgen et al 26 , and agrees with the overall climate-induced migration of ectomycorrhiza fungi [1][2][3][4] . The lower suitability for the Périgord truffle corresponds with the species' current restriction to southern Europe 23 .…”
Section: Discussionsupporting
confidence: 90%
“…However, our models suggest that the very strong temperature increase under the high-emission scenario (RCP8.5), together with the cumulative likelihood of summer droughts 27 , will suppress fruit body formation (and thus total production) 20 , regardless of the sporocarp's ability to survive under extreme aridity. Hence, we expect that the most favourable climate conditions will move northward, which coincides with the predicted latitudinal shift reported in Büntgen et al 26 , and agrees with the overall climate-induced migration of ectomycorrhiza fungi [1][2][3][4] . The lower suitability for the Périgord truffle corresponds with the species' current restriction to southern Europe 23 .…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, fungal community diversity and species richness were both higher in the rhizosphere compared to the phyllosphere, which is in agreement with an earlier study ( Park et al, 2017 ). One study reported that tree traits can affect the patterns of fungal richness in leaves ( Andrew et al, 2019 ). In our study, root properties were the dominate factor that influenced phyllosphere fungal diversity, while soil properties indirectly affected phyllosphere fungal diversity ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phenology studies are increasingly used to investigate how plants and animals are responding to current climate change and to predict how they may respond to future climate change (e.g., Wolkovich et al., ; Zohner and Renner, ; Andrew et al., ). How plants respond to changing patterns of temperature and precipitation has major implications for agriculture, forestry, growing season dynamics, and ecosystem processes (Tang et al., ).…”
mentioning
confidence: 99%